2017
DOI: 10.1111/dth.12479
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrant hypertrophic herpes genitalis in HIV-infected patient successfully treated with topical imiquimod

Abstract: Herpes Simplex Virus type 2 is the primary cause of genital ulceration worldwide. The presence of atypical features like deep ulcerations, hypertrophic, or pseudotumoural lesions or unusual location can be a marker for co-infection with HIV. These immunocompromised patients are usually resistant to the conventional antiviral treatment. We present a case of an HIV-infected patient with hypertrophic herpes genitalis, refractory to conventional oral antiviral therapy, who was successfully treated with a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…Foscarnet and cidofovir are nephrotoxic medications that require intensive laboratory monitoring and infectious disease specialist consultation. Imiquimod 5% applied to the lesion for 8 hours 3 times/week until clinical resolution is an alternative that has been reported to be effective ( 510 , 511 ). Topical cidofovir gel 1% can be applied to lesions 2–4 times daily; however, cidofovir must be compounded at a pharmacy ( 512 ).…”
Section: Diseases Characterized By Genital Anal or Perianal Ulcersmentioning
confidence: 99%
“…Foscarnet and cidofovir are nephrotoxic medications that require intensive laboratory monitoring and infectious disease specialist consultation. Imiquimod 5% applied to the lesion for 8 hours 3 times/week until clinical resolution is an alternative that has been reported to be effective ( 510 , 511 ). Topical cidofovir gel 1% can be applied to lesions 2–4 times daily; however, cidofovir must be compounded at a pharmacy ( 512 ).…”
Section: Diseases Characterized By Genital Anal or Perianal Ulcersmentioning
confidence: 99%
“…Vulvar herpes is usually characterized by the presence of acute vesicles and erosions. However, atypical presentations including pseudotumoral herpes, also designated as tumor-like ( Ranu et al, 2011 ) or hypertrophic ( Holmes et al, 2007 ; Leevaphan et al, 2015 ; Tandon et al, 2017 ) lesions, have been reported. Chronic genital pseudotumoral herpes has only been described in immunocompromised—mainly HIV positive—male or female patients.…”
Section: Discussionmentioning
confidence: 99%
“…The HSV-2 seroprevalence in the United States is 12.1% ( McQuillan et al, 2018 ). Immunocompromised patients, especially with HIV infection, are at an increased risk for acyclovir-resistant HSV infection, which has been reported to cause anogenital pseudotumors in this population ( Tandon et al, 2017 ; Ranu et al, 2011 ; Sbidian et al, 2013 ). However, HSV-2 acyclovir resistance is rare in immunocompetent individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Imiquimod is approved as a 5% topical cream to treat genital warts and is sometimes used as a topical immunostimulant to treat acyclovir-resistant or recalcitrant genital herpes infection (51)(52)(53). Therefore, we wanted to test whether it stimulates the production of TNF-␣ in endocervical epithelial cells with additional experiments.…”
Section: Fig 1 Establishment Of Cell Models (A)mentioning
confidence: 99%